Family Support Moderates the Relationship Between Pregnancy Stress, Depressive Symptoms, and Insomnia - Liu S; Huang M; Zhang F; Tao J; Wen D; Deng W; Lin Y; Zhang P; Li M (Nature and Science of Sleep)
ShanYan Liu,1 Meijiao Huang,2 FengYing Zhang,2 Jing Tao,1 Dan Wen,1 WeiYuan Deng,1 YaoHua Lin,3 Ping Zhang,2 Min Li2 1The Affiliated Nanhua Hospital, Department of Obstetrics, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China; 2The Affiliated Nanhua Hospital, Department of Neurology, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China; 3The First Affiliated Hospital, Institute of Obstetrics, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of ChinaCorrespondence: Ping Zhang; Min Li, The Affiliated Nanhua Hospital, Department of Neurology, Hengyang Medical College, University of South China, Hengyang, Hunan, 421002, People’s Republic of China, Email 516387382@qq.com; lim-usc@qq.comObjective: Insomnia is a common issue that pregnant women often have to deal with. This study seeks to examine the connections between pregnancy stress, depressive symptoms, family support, and insomnia symptoms.Methods: Convenience sampling was employed to recruit 1049 valid participants. The primary measurement tools utilized were the Pregnancy Stress Scale, the Family Support Subscale, and the Patient Health Questionnaire-2. Data analysis was conducted using SPSS 24.0 software. Using binary logistic regression to verify the independent effects of pregnancy stress, depression symptoms, and family support on insomnia symptoms. PROCESS macro Model 4 was applied to assess the mediating effect, while PROCESS macro Model 5 was used to evaluate the moderating effect.Results: The overall prevalence of insomnia symptoms and depressive symptoms among pregnant women was 54% (n=572) and 20% (n=207) in this study. Pregnancy stress, depressive symptoms and family support positively affect insomnia symptoms. The indirect effect of depressive symptoms between pregnancy stress and insomnia symptoms was significant, with the mediator proportion of 45.16%. As moderator, family support weakens the impact of pregnancy stress on insomnia symptoms.Conclusion: Increased pregnancy stress and increased depressive symptoms could trigger insomnia symptoms. Depressive symptoms mediated the path from between pregnancy stress and insomnia symptoms. Family support weakened the link between pregnancy stress and insomnia symptoms. These findings can assist pregnant women in managing stress more effectively and improving their mental well-being.Keywords: depressive symptoms, family support, insomnia symptoms, pregnancy stress, pregnant woman